The effectiveness of CALL in helping Persian L2 learners produce the English vowel /p - Rahimi, Meisam; Tavakoli, Mansoor (Penerbit UKM, 2015)
Recent research in pronunciation training has indicated a growing interest in the application of computer-based speech-production techniques. This paper tries to evaluate the effectiveness of a console-based Praat script that utilizes acoustic data in real time to help Persian L2 learners to improve their production of the English vowel /ɒ/. This vowel is not among the Persian vowels and believed to be difficult for Persian learners of English to perceive and produce. A group of 30 Persian ESL learners was recruited - 15 learners were randomly assigned to the experimental group and 15 to the control group. Over a three-week period, the experimental group received acoustic-articulatory training and was exposed to the CALL software for receiving acoustic feedback, while the control group was exposed only to auditory input on the target sound. The groups were given a pretest to ensure their comparability, an immediate posttest to evaluate the effectiveness of the feedback provided and a generalization test to see whether the participants were able to generalize the possibly developed knowledge to new contexts. The results of the study showed a significant improvement in the performance of the participants in experimental group in terms of both the posttest and the generalization test. These findings lend support to the feasibility of the use of much simpler and more available CALL tools than those reported in previous research for foreign language segmental acquisition and its effectiveness in generalization of the acquired skills to new contexts.